Taxonomy of the genus Meleonoma Meyrick, 1914 (Lepidoptera: Autostichidae) from China (IV), with descriptions of twelve new species - Zhu, Xiaoju; Wang, Shuxia (Zootaxa, 2022)
Twelve new species of the genus Meleonoma Meyrick are described. Meleonoma aculeolata sp. nov. and M. rectivalva sp. nov. belong to the acutiuscula species-group; M. robustijuxta sp. nov. and M. varilobata sp. nov. belong to the jigongshanica species-group; M. basitriangula sp. nov., M. biprocessa sp. nov., M. curvicornuta sp. nov., M. dilatilobata sp. nov., M. globulosa sp. nov., M. prospina sp. nov., M. sinuata sp. nov. and M. unijugata sp. nov. belong to the puncticulata species-group. Images of both adults and genitalia are provided.